Pengaruh Media Sosial, Gaya Hidup Dan Literasi Keuangan Terhadap Perilaku Konsumtif (Studi Kasus Mahasiswa FEBI UIN Sumatera Utara) - Irma Yunita; Fauzi Arif Lubis; Nuri Aslami (CV. ITTC INDONESIA, 2023)
The purpose of this study was to determine the effect of social media, lifestyle and financial literacy on consumptive behavior in FEBI UINSU students, either partially or simultaneously. This study uses quantitative methods. The population in this study was the 2018 FEBI UINSU students. The sampling technique used was purposive sampling with a total sample of 92 respondents. Data collection techniques using a questionnaire. The primary data obtained were analyzed through the IBM SPSS statistic 25 program. The results showed that first, social media had a positive and significant effect on consumptive behavior in FEBI UIN-SU students with a significant value of 0.005 < 0.05. Second, lifestyle has a positive and significant effect on consumptive behavior in FEBI UIN-SU students with a significant value of 0.000 < 0.05. Third, financial literacy has a positive and significant effect on consumptive behavior in FEBI UIN-SU students with a significant value of 0.001 < 0.05. Fourh, simultaneously social media, lifestyle and financial literacy have a significant effect on consumptive behavior with a significant value < 0.05, namely 0.040 < 0.05.